The General Administrative Procedure Act after Legislative Decree No. 1272: ten pending amendments for a more predictable public administration - Montenegro Monteza, Favio Martín (2025)
The article examines the reforms introduced by Legislative Decree No. 1272 to Peru’s General Administrative Procedure Law (LPAG) and proposes ten amendments to enhance its effectiveness and predictability. Key suggestions include: extending expiration rules to the appeal stage, applying LPAG provisions to oversight activities, suspending all measures when appeals are filed, reinforcing reasoning in administrative acts, safeguarding the use of reconsideration, clarifying the scope of voluntary correction, standardizing measure terminology, fixing the tax unit (UIT) based on the date of the offense, regulating mitigating factors for non-monetary sanctions, and removing the requirement for new evidence in certain reconsiderations. These improvements aim to reduce arbitrariness, ensure legal certainty, and optimize administrative performance.